Gastroesophageal Reflux Disease in Push Up and Sit Up Exercise - B J Waleleng; D Takaendengan; N Tendean W (The Indonesian Society for Digestive Endoscopy, 2007)
Background: Several factors involve in GERD are hypotension of Lower Esophageal Sphincter (LES), Transient Lower Esophageal Sphincter (TLES) relaxation, delayed gastric emptying and esophageal hiatal hernia. Bent over and supine position like push up and sit up exercise in this study, are known as trigger factors for GERD which can cause hypotension of the LES, TLES relaxation and transdiaphragmatic pressure resulted in increased diaphragmatic nerves activation. Aim: The purpose of this study was to investigate the occurrence of GERD in push up and sit up exercise. Materials and Methods: This is an experimental study; subjects were healthy male aged 18-21 years. Patients data were collected after fulfilling the selection criteria as described in the study protocol. χ2 analysis or Fischer’s exact test analysis was applied to determine the statistical significance of difference between push up and sit up. There were 30 subjects in the study, 15 subjects in push up group and 15 subjects in sit up group. Result: Three subjects (10%) were dropped out and 27 subjects (90%) were endoscopied. In the sit up group, 13 subjects (87%) were endoscopied, 9 subjects (70%) had normal endoscopy and 4 subjects (30%) had mucosal breaks. In push up group, 14 subjects (93%) were endoscopied, 6 subjects (43%) had normal endoscopy and 8 subjects (57%) had mucosal breaks. There was no significant difference between push up and sit up group with χ2 analysis or Fischer’s exact test (p = 0.322). Conclusion: There was more likely GERD in push up group than in sit up group, but the difference was not significant. Keywords: push up exercise; sit up exercise, gastroesophageal reflux disease (GERD)